Pineapple waste-silages as basal feed for growing Boer X Kacang cross goats - Ginting, Simon P; Krisnan, Rantan; Simanihuruk, Kiston (Indonesian Journal of Animal and Veterinary Sciences, 2007)
The study was aimed: 1) to evaluate the effects of using different additives on the quality of pineapple waste-silage (SLN), and 2) to investigate the responses of goats fed with PAS as a basal feed. Pineapple processing wastes include skins and the pulp left after cannery wastes are pressed to extract the juice. Six additive treatments were used in the processing of pressed pineapple wastes, namely 1) urea (5% DM), 2) Urea (2% DM) and cassava meal (3% DM), 3) molasses (5% DM), 4) urea (2.5% DM) and molasses (2.5% DM), 5) fermented-juice lactic acid bacteria (5% DM), and 6) without additives. Fermentation periode were set at 9, 12, 15, 18 and 21 days. The best SLN obtained from those treatments was then used in feeding trials. Twenty male Boer x Kacang crosses with an initial body weight averaging 13.2 Â± 1.9 kg were used in this experiment. The animals were allocated to one of the following feed treatments, in DM: A) Grasses (75%) + SLN (25%), B) SLN (75%) + Concentrates (25%), C) SLN (50%) +Concentrate (50%), and D) SLN (25%) + Concentrates (75%). Using molasses as additive material at 5% and 15 days of fermentation period gave the best chemical and physical characteristics of the SLN. Its crude fiber content decreased and it showed the lowest pH (4.7) The silage showed temperature at 280C, and its taste was sour, and no fungi contamination. The DM and OM intakes and DM, OM and N digestibility were not different (P>0.05) between the animals fed 75% Grass/25% CON and 75% SLN/25% CON. When the proportion of concentrates in the rations was increased, the feed intake and digestibility were increase significantly (P<0.05). ADG (71.3 vs 68.8 g) and feed efficiency (11.2 vs 13.4) was similar between the 75% Grass/25% CON and 75% SLN 25% CON groups. ADG increased significantly (P<0.05) when the proportion of concentrates in ration was increased to 50% (82.6 g) or to 75% (89.1 g). N retention was positive in all treatments, and it was increased significantly (P<0.05) as the proportion of concentrates in ration increased. It is concluded that pineapple wastes could be preserved to silages using molasses as additive material. Pineapple waste silage could be used as roughage to substitute grass in ration. When fed with the pineapple waste silage the responses of goats will increase as the proportion of concentrates in the ration increased. Key Words: Pineapple Wastes, Silages, Goats